1996
DOI: 10.1148/radiology.200.3.8756926
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal masses: correlation between CT attenuation value and chemical shift ratio at MR imaging with in-phase and opposed-phase sequences.

Abstract: CT attenuation values are highly correlated with chemical-shift ratios. Both values were indeterminate for a similar subset of benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(50 citation statements)
references
References 0 publications
1
47
0
2
Order By: Relevance
“…Usually, malignant masses are hypointense on T1-weighted images and hyperintense on T2-weighted images, with strong enhancement after contrast injection and delayed washout. More recent studies have used the lipid content of adenomas, which causes a loss in signal intensity on chemical-shift MRI (Outwater et al 1995(Outwater et al , 1996. However, MRI may be helpful in the diagnosis of pheochromocytoma, where it outperforms CT scanning.…”
Section: Imaging Of Adrenal Incidentalomamentioning
confidence: 99%
“…Usually, malignant masses are hypointense on T1-weighted images and hyperintense on T2-weighted images, with strong enhancement after contrast injection and delayed washout. More recent studies have used the lipid content of adenomas, which causes a loss in signal intensity on chemical-shift MRI (Outwater et al 1995(Outwater et al , 1996. However, MRI may be helpful in the diagnosis of pheochromocytoma, where it outperforms CT scanning.…”
Section: Imaging Of Adrenal Incidentalomamentioning
confidence: 99%
“…1a,b). Other investigators subsequently confirmed the value of this technique (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Magnetic Resonance Imaging (Mri) Techniquesmentioning
confidence: 80%
“…Any signal present on the subtracted image indicates the presence of lipid and water protons within the same voxel (24). If one wanted to perform a quantitative measurement of adrenal lesion lipid then the chemical shift index can be calculated (21). The chemical shift index is defined as follows: A chemical shift index of >15%-20% detects most lipid-containing adrenal adenomas with high specificity (13,23,25).…”
Section: Magnetic Resonance Imaging (Mri) Techniquesmentioning
confidence: 99%
“…In the case of metastases or nodules other than adenomas, because of their poor lipid content, signal drop is irrelevant. 30,31 Therefore, in the absence of a history of malignancy, a small, oval, homogeneous, lipid-containing mass, with regular margins showing mild or no enhancement can be confidently diagnosed as adenoma (benign incidentaloma) and might not require additional radiological investigation. If the lipid content of the mass is slight or absent, a 6-to 12-month imaging follow-up is generally considered sufficient to diagnose a "notevolving" (or steady) adrenal lesion.…”
Section: Adenomamentioning
confidence: 99%